Cognitive and affective theory of mind in female patients with borderline personality disorder - Spieß, Karen; Neukel, Corinne; Krauch, Marlene; Spohn, Angelika; Schnell, Knut; Herpertz, Sabine; Bertsch, Katja (Journal of personality disorders, 2021)
Empirical studies have identified deficits in cognitive and affective theory of mind (ToM) in patients with borderline personality disorder (BPD), but results remain heterogeneous and not much is known about the role of childhood trauma. The current study assessed cognitive and affective ToM in 80 patients with BPD and 41 healthy controls in a false-belief cartoon task. Childhood trauma was measured with the Childhood Trauma Questionnaire (CTQ). Patients with BPD responded slower in all experimental conditions in false-belief situations, but not when false beliefs were resolved; made more errors in the cognitive ToM condition; and reported worse affective states more often in and after false-belief situations. No significant correlations between ToM and childhood trauma could be found. The current study revealed deficits in cognitive and affective ToM in patients with BPD that may be related to a more negative affective state raised by the false-belief stories.
Gesehen am 16.11.2021